2003
DOI: 10.1515/jnetdy.2003.020
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamically Consistent Relaxation Model for Turbulent Binary Mixture Undergoing Phase Transition

Abstract: Non-equilibrium phenomena within a turbulent binary mixture undergoing a phase transition are modelled based on the one fluid, homogeneous approach. The set of governing evolution equations is given and the averaged basic balance laws are considered. The continuum under consideration consists of two constituents of which the first is undergoing a phase transition (vaporisation, cavitation, flashing, condensation) during the flow with turbulent transport of mass, heat and momentum. Starting from the Clausius-Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…The neoclassical statement offers value for constitutive relations. The first is an entropy flux, and the second is a volume flux vector (see Equations (63) and (64)). In addition, connections between the heating and working fluxes as well as with the entropy, volume, and momentum fluxes are not simple (Equations (24) and (25)); they can be extended to the cases where Cimmelli's interstitial heating and interstitial working vectors appear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The neoclassical statement offers value for constitutive relations. The first is an entropy flux, and the second is a volume flux vector (see Equations (63) and (64)). In addition, connections between the heating and working fluxes as well as with the entropy, volume, and momentum fluxes are not simple (Equations (24) and (25)); they can be extended to the cases where Cimmelli's interstitial heating and interstitial working vectors appear.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that it is possible to adopt the Gyftopoulos-Beretta exposition for a continuum media like a Navier-Stokes fluid. We are now enforcing this exposition to the case of turbulent fluid, where, as we suppose [64], the classical model of Osborne Reynolds needs some thermodynamic reconsiderations. For instance, if one takes a so-called k − ε model as a well-known phenomenological model of turbulent momentum evolution, then the question becomes, "Which role for two scalar evolution equations k and ε is proper?"…”
Section: Further Possibilities Of the Gyftopoulos-beretta Expositionsmentioning
confidence: 96%
See 1 more Smart Citation
“…However, if we suppose that the surface tension c is a surface dependent quantity, for instant, Bilicki and Badur (2003):…”
Section: Constitutive Relations For Surface Momentum Fluxmentioning
confidence: 99%
“…where s-is the Bilicki-Kestin relaxation time (Bilicki and Badur 2003). Next, using the surface mass balance…”
Section: Constitutive Relations For Surface Momentum Fluxmentioning
confidence: 99%